Graphene–Silicon Layered Structures on Single‐Crystalline Ir(111) Thin Films. Issue 3 (20th January 2015) - Que, Yande; Zhang, Yong; Wang, Yeliang; Huang, Li; Xu, Wenyan; Tao, Jing; Wu, Lijun; Zhu, Yimei; Kim, Kisslinger; Weinl, Michael; Schreck, Matthias; Shen, Chengmin; et al.
<x xml:space="preserve">Abstract</x> Single‐crystalline transition metal films are ideal playing fields for the epitaxial growth of graphene and graphene‐based materials. Graphene–silicon layered structures are successfully constructed on Ir(111) thin films on Si substrates with an yttria‐stabilized zirconia buffer layer via intercalation approach. Such heterolayered structures are compatible with the current Si‐based microelectronic technique, showing high promise for applications in future micro‐ and nanoelectronic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>